Photoinduced multicomponent regioselective synthesis of 1,4,5-trisubstituted-1,2,3-triazoles: transition metal-, azide- and oxidant-free protocol - Sai Allaka, Bhargava; Basavoju, Srinivas; Rama Krishna, Gamidi (Advanced Synthesis & Catalysis, 2021)
A transition metal- and azide-free approach is explored to synthesize 1,4,5-trisubstituted-1,2,3-triazoles under sunlight. The reaction proceeds via C-N and N-N bond formations. These regioselective 1,2,3-triazoles are obtained from isatin Schiff bases, benzaldehydes and tosylhydrazine in the presence of base. This protocol offers the structurally diverse 1,2,3-triazole derivatives with 75-90% yields.
Keywords: 1; 2; 3-triazoles; 4; 5-trisubstituted-1; azide- and oxidant free protocol; Cycloaddition; milder reaction conditions; molecular diversity; Multicomponent reaction; Regioselectivity; transition metal-